Proceedings of the First International Conference on Computational Intelligence and Informatics ICCII 2016 - Satapathy, Suresh Chandra; Prasad, V. Kamakshi; Rani, B. Padmaja; Udgata, Siba K.; Raju, K. Srujan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
The book covers a variety of topics which include data mining and data warehousing, high performance computing, parallel and distributed computing, computational intelligence, soft computing, big data, cloud computing, grid computing, cognitive computing, image processing, computer networks, wireless networks, social networks, wireless sensor networks, information and network security, web security, internet of things, bioinformatics and geoinformatics. The book is a collection of best papers submitted in the First International Conference on Computational Intelligence and Informatics (ICCII 2016) held during 28-30 May 2016 at JNTUH CEH, Hyderabad, India. It was hosted by Department of Computer Science and Engineering, JNTUH College of Engineering in association with Division V (Education & Research) CSI, India. .
Chapter 1. GUI Based Automated Data Analysis System Using Matlab® -- Chapter 2. A Survey Study on Singular Value Decomposition and Genetic Algorithm Based on Digital Watermarking Techniques -- Chapter 3. A Robust Authenticated Privacy-Preserving Attribute Matchmaking Protocol for Mobile Social Networks -- Chapter 4. Artificial Neural Networks Model to Improve the Performance Index of the Coil-disc Assembly in Tube Flow -- Chapter 5. Handling Wormhole Attacks in WSNs Using Location Based Approach -- Chapter 6. Video Authentication Using Watermark and Digital Signature - A Study -- Chapter 7. A Comparative Study and Performance Analysis Using IRNSS and Hybrid Satellites -- Chapter 8. Generalized Approach to Enhance the Shared Cache Performance in Multicore Platform -- Chapter 9. A Novel Framework for Road Traffic Data Management for Cloud Based Storage -- Chapter 10. Minimum Description Length (MDL) Based Graph Analytics -- Chapter 11. Implementation of Intrusion Detection System Using Artificial Bee Colony with Correlation Based Feature Selection -- Chapter 12. Virtualization Security Issues and Mitigations in Cloud Computing -- Chapter 13. Secured Three-tier Architecture for Wireless Sensor Networks Using Chaotic Neural Network -- Chapter 14. A Regularized Constrained Least Square De-blurring Method for SPECT Images -- Chapter 15. Effective Video Data Retrieval Using Image Key Frame Selection -- Chapter 16. A Review of Joint Channel Assignment and Routing Protocols for Wireless Mesh Networks -- Chapter 17. Correlated Cluster Based Imputation for Treatment of Missing Values -- Chapter 18. Application of Pseudo 2-D Hidden Markov Model for Hand Gesture Recognition -- Chapter 19. Cleaning and Sentiment Tasks for News Transcript Data -- Chapter 20. Inventory Management System Using IOT -- Chapter 21. A Personalized Recommender System Using Conceptual Dynamics -- Chapter 22. Mitigating Replay Attack in Wireless Sensor Network through Assortment of Packets -- Chapter 23. Progressive Genetic Evolutions Based Join Cost Optimization (PGE-JCO) for Distributed RDF Chain Queries -- Chapter 24. Improved Apriori Algorithm Using Power Set on Hadoop -- Chapter 25. Distributed Cooperative Algorithm to Mitigate Hello Flood Attack in Cognitive Radio Ad-hoc Networks (CRAHNs) -- Chapter 26. Performance Comparison of Intentional Caching Schemes in Disruption Tolerant Networks (DTN) -- Chapter 27. A Cascaded Method to Reduce the Computational Burden of Nearest Neighbor Classier -- Chapter 28. An Innovative method to Mitigate DDoS Attacks for Cloud Environment using Bagging and Stacking -- Chapter 29. A Novel Method for QoS Based Spectrum Allocation in Cognitive Radio Systems -- Chapter 30. A Review on fMRI Signal Analysis and Brain Mapping Methodologies -- Chapter 31. Static Program Behavior Tracing for Program Similarity Quantification -- Chapter 32. Ontology Based Automatic Annotation: An Approach for Efficient Retrieval of Semantic Results of Web Documents -- Chapter 33. An Iterative Hadoop Based Ensemble Data Classification Model on Distributed Medical Databases -- Chapter 34. A Framework for Secure Mobile Cloud Computing -- Chapter 35. Intelligent Evaluation of Short Responses for e-Learning Systems -- Chapter 36. Content Based Video Retrieval Using Dominant Color and Shape Feature -- Chapter 37. Intelligent SRTF: A New Approach to Reduce the Number of Context Switches in SRTF -- Chapter 38. Anomaly Detection Using New Tracing Tricks on Program Executions and Analysis of System Data -- Chapter 39. Aesthetics of Bharatanatyam Poses Evaluated through Fractal Analysis -- Chapter 40. Algorithm to Find the Dependent Variable in Large Virtualized Environment -- Chapter 41. Challenges of Modern Query Processing -- Chapter 42. IOT-Based Traffic Signal Control Technique for Helping Emergency Vehicles -- Chapter 43. Wireless Sensor Sequence Data Model for Smart Home and IoT Data Analytics -- Chapter 44. Automatic Detection of Violent Scenes in Tollywood Movies - A Rough Set Approach -- Chapter 45. Prism Tree Shape Representation Based Recognition of Offline Tamil Handwritten Characters -- Chapter 46. The Emergence of Internet Protocol Television as Next Generation Broadcast Network -- Chapter 47. Cognition-as-a-Service: Arbitrage Opportunity of Cognition Algorithms in Cloud Computing -- Chapter 48. Directional Area Based Minutiae Selection and Cryptographic Key Generation Using Biometric Fingerprint -- Chapter 49. Combined Effect of Soft Computing Methods in Classification -- Chapter 50. Weighted Co-Clustering Approach for Heart Disease Analysis -- Chapter 51. Secure User Authentication with Graphical Passwords and PassText -- Chapter 52. A Novel Hybrid Fuzzy Pattern Classifier Using Order Weighted Averaging -- Chapter 53. Efficient Query Analysis and Performance Evaluation of the NoSQL Datastore for BigData -- Chapter 54. Performance Evaluation of QoS Aware Routing Protocols in Wireless Sensor Networks -- Chapter 55. Agent Based QoS Routing for Intrusion Detection of Sinkhole Attack in Clustered Wireless Sensor Networks -- Chapter 56. An Efficient Probability of Detection Model for Wireless Sensor Networks -- Chapter 57. Incremental Updating of Mined Association Rules for Reflecting Record Insertions -- Chapter 58. Pattern Anonymization: Hybridizing Data Restructure with Feature Set Partitioning for Privacy Preserving in Supervised Learning -- Chapter 59. Effective Visiting Schedule Generation in a Tourist Recommender System Using Hadoop -- Chapter 60. A Study and Mapping of Radiation Levels from Mobile Towers in and Around Bangalore -- Chapter 61. Low Cost Smart Watering System in Multi Soil and Multi Crop Environment Using GPS and GPRS -- Chapter 62. An Image Encryption Technique Using Scan Based Approach and Image as Key -- Chapter 63. IPMOntoShare: Merging of Integrated Pest Management Ontologies -- Chapter 64. An Approach for Knowledge Based Word Sense Disambiguation -- Chapter 65. Enhanced Scaffold Design Pattern for Malleable Multi-Tenant SaaS Application -- Chapter 66. Modeling of Three Phase Asynchronous Motor Using Vector Control Theory -- Chapter 67. Lecture Notes in Computer Science: An Unsupervised Classification of Printed and Handwritten Telugu Words in Pre-printed Documents Using Text Discrimination Coefficient -- Chapter 68. Neural Nets for Thermodynamic Properties -- Chapter 69.< Parallelization of Synthetic Aperture Radar (SAR) Image formation Algorithm.
Keywords: Computational intelligence; Telecommunication; Bioinformatics; Computational Intelligence; Communications Engineering, Networks; Computational and Systems Biology